Odnos slovenskih potrošnikov do mobilnega oglaševanja - Oven, Sašo (Teorija in praksa, 2012)
This paper addresses the use of mobile technology as a new medium for interactive digital advertising. It also addresses consumer attitudes to mobile advertising. The paper's purpose is to present key factors affecting Slovenian consumers' attitudes to mobile advertising and the potency of future advertising strategies that would enhance the user experience of mobile advertising. Based on previous experiences with mobile advertising among Slovenian consumers the paper also addresses the consequences of the inappropriate behaviour of advertisers and mobile providers. Our research model adapts and extends the conceptual model/framework of SMS advertising that was tested on Finnish consumers. The data were analysed with multivariate statistical methods and the majority of hypotheses were confirmed in the analysis. The results may serve as a basis to help advertisers improve their mobile advertising strategies.
Keywords: Advertising; Oglaševanje; Mobile communications; Mobilne komunikacije; Potrošniki; Consumers; Attitudes; Stališča; Vedenje potrošnikov; Consumer behavior; Slovenia; Slovenija; komunikacijska tehnologija